Penanaman Sikap Sosial Melalui Pembelajaran PKN Pada Siswa Kelas V Di SDN Karang Tengah 1 Kota Tangerang - Nurlayali, Hilwatunnisa; Sunardin, Sunardin; Gumilar, Aris (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to examine the cultivation of social attitudes through Civic Education (PKn) learning among 5th-grade students at SDN Karang Tengah 1. To achieve its objectives, the study establishes three primary goals: firstly, to comprehend the process of cultivating social attitudes through PKn education within the environment of SDN Karang Tengah 1; secondly, to identify the challenges that arise in the effort of instilling these social attitudes; and thirdly, to unveil the strategies applied to address these challenges in the process of fostering social attitudes through PKn education. The findings of this research reveal that the cultivation of social attitudes among 5th-grade students at SDN Karang Tengah 1 can be effectively achieved through the PKn learning approach. The role of teachers in providing positive role models to students, both within and outside the classroom, proves to be pivotal in internalizing and practicing these social values. However, the study also identifies challenges in the form of certain students being tempted to engage in cheating behaviors during assignments. Solutions to these challenges involve firm measures taken by teachers, including reprimanding involved students and the subsequent positive response from these students, demonstrated through apologies and acknowledgments of their mistakes. This research provides a comprehensive insight into the potential of PKn education as an effective tool in shaping social attitudes at the primary education level. By identifying barriers and their mitigating strategies, the study underscores the crucial role of teachers in guiding students' social development and offers valuable input for the development of holistic learning approaches that center on the cultivation of citizenship values.